2015
DOI: 10.1590/s1413-70542015000400001
|View full text |Cite
|
Sign up to set email alerts
|

EFFECTIVENESS OF POSTHARVEST SOLUTIONS FOR THE CONSERVATION OF CUT Oncidium varicosum (ORCHIDACEAE) INFLORESCENCES

Abstract: The orchid Oncidium varicosum is a tropical plant with significant commercial value due to the beauty of its yellow inflorescences. Several authors have observed a reduction in the water content of cut flowers, consequently, wilting and senescence of petals are the main reasons for the termination of the decorative life of cut flowers. In this research, we studied the effects of several chemical compounds on the postharvest life of cut inflorescences of Oncidium varicosum 'Samurai'. These chemicals are as foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 17 publications
0
4
0
7
Order By: Relevance
“…The preservative solution containing AgNO3 (250 ppm) + sucrose (3%) not only increase vase life but also helps in improving flower opening percentage, days to open basal floret, bloom spread, floret length, floret diameter, floral spike fresh and dry weight, and fresh weight loss. Similarly pulsing of cut flowers with sucrose and biocides combination increased floret opening in lisianthus (Kiamohammadi and Hashemaabadi, 2011), bird of paradise (Gendy and Hamad, 2011), orchid (Mattiuz et al, 2015), tuberose (Kumar and Deen, 2017) and gladiolus (Casares et al, 2017). Like floret opening percentage, Ahmed et al (2018) observed that biocide (Aluminium sulphate) and sucrose induce early opening of basal florets in Gladiolus hybridus.…”
Section: Discussionmentioning
confidence: 94%
“…The preservative solution containing AgNO3 (250 ppm) + sucrose (3%) not only increase vase life but also helps in improving flower opening percentage, days to open basal floret, bloom spread, floret length, floret diameter, floral spike fresh and dry weight, and fresh weight loss. Similarly pulsing of cut flowers with sucrose and biocides combination increased floret opening in lisianthus (Kiamohammadi and Hashemaabadi, 2011), bird of paradise (Gendy and Hamad, 2011), orchid (Mattiuz et al, 2015), tuberose (Kumar and Deen, 2017) and gladiolus (Casares et al, 2017). Like floret opening percentage, Ahmed et al (2018) observed that biocide (Aluminium sulphate) and sucrose induce early opening of basal florets in Gladiolus hybridus.…”
Section: Discussionmentioning
confidence: 94%
“…Xylem occlusion may be related to blockage of the xylem vessels, resulting from the entry of air in cut stems (air emboli) or the accumulation of microorganisms in vascular system (van Doorn, 1999;Mattiuz et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…In Heliconia wagneriana, a 10% sucrose pulsing for 60 minutes maintained the quality of the inflorescences 20% longer than in control stems that had high transpiration and low water consumption (Costa et al, 2015). In Oncidium varicosum orchids a 5% sucrose + 100 mg L -1 8-HQC + 50 mg L -1 AgNO 3 vase solution maintained the relative water content and the carbohydrates and soluble sugars content in the flowers, thus preserving the vase life for longer compared to stems of a control treatment (Mattiuz et al, 2015).…”
Section: Experiments 4 -Evaluation Of Solutions For Pulsingmentioning
confidence: 95%